Spanish Phrase Finder (Harper Collins Publishers, 1993)
Collins Gem Phrase Finders are designed for ease of use with over 70 topics listed alphabeticlly. The short simple phrases can be tailored to suit your own situation.
Consultant by Rugama, Isabel
Keywords: Spanish language